Effects of open- and self-pollination on fruit set and seed quality in Jatropha curcas L. - Nurul Hidayah Che Mat; Nisha Thopla Govender; Zahira Yaakob; Wickneswari Ratnam (Penerbit Universiti Kebangsaan Malaysia, 2019)
Investigation on different mating systems is necessary to improve fruit and seed production and seed quality in Jatropha curcas. In the present study, a total of 150 female flowers belonging to five accessions from Indonesia and Malaysia were screened for traits associated with fruit set and seed quality under open- and self-pollination. The study was conducted at Biodiesel Research Station, Universiti Kebangsaan Malaysia (UKM), Kuala Pilah from April to September 2015. The number of fruits per plant (NFP), number of seeds per plant (NSP) and number of seeds germinated (NSG) showed significant differences among the mating systems. Under open-pollination, the maximum mean values for NFP, NSP, NSG and number of seedlings surviving after three months (NSS) were 10, 29, 27 and 18, respectively. Conversely, self-pollination scored at 9, 26, 22 and 18 for NFP, NSP, NSG and NSS, respectively. Seed weight (SWt) showed significant differences among accessions whereas seed length (SLT) showed significant differences among the mating systems and accessions. UKMJC20 (Indonesia) showed the best performance in terms of NFP under both open- and self-pollination whereas UKMJC21 (Malaysia) showed the best performance in terms of SWt and SLT under both conditions. Two (UKMJC13 and UKMJC21) out of five accessions showed occurrence of apomixis.